Examining the Role of Policy and Leadership Behavior in Shaping Educational Quality - Ibnu Fitrianto; Nurhuda Alfina Layalin; H. Cooper (Innovative Journal of Educational Research and Insights, 2025)
This study examines the interconnected role of policy frameworks and leadership behavior in shaping educational quality within contemporary school systems. Using a qualitative design supported by document analysis and thematic interpretation, the research explores how leadership practices interact with governance structures, policy mandates, and institutional contexts to influence school performance. Findings reveal that effective educational leadership is not merely a function of individual leadership styles but is deeply shaped by policy implementation dynamics, organizational culture, and the broader sociopolitical environment. The study also highlights key challenges faced by school leaders in translating policy goals into meaningful instructional improvements, particularly amid increasing accountability pressures and rapid educational transformations. Overall, the research underscores the need for integrated policy–leadership approaches that align strategic vision, governance structures, and evidence-based practices to sustainably enhance educational outcomes.